Refined Approaches to Evaluating the Robustness of Lightweight Symmetric Ciphers Against Differential-Linear Cryptanalysis - Tsemma Dmytro Oleksandrovych (ХНУРЕ, 2025)
The protection of data in devices with limited computational capabilities — such as IoT sensors, embedded controllers, and smart identification systems — relies heavily on lightweight cryptographic algorithms. The emergence of the NIST Lightweight Cryptography standardization initiative has reinforced the importance of developing energy-efficient and secure cryptographic primitives. However, even optimized lightweight ciphers must maintain resilience to complex hybrid attacks like differential-linear cryptanalysis. This study explores modern approaches for assessing the robustness of lightweight symmetric ciphers against such attacks, highlighting structural factors influencing cipher security and presenting strategies for their enhancement. In addition to identifying vulnerabilities, the paper emphasizes the importance of integrating automated analysis tools for evaluating cipher resistance. By combining formal mathematical models with empirical testing on reduced cipher versions, researchers can achieve a more accurate understanding of security margins. The proposed approach not only supports the design of future lightweight algorithms but also provides practical guidance for developers implementing cryptographic protection in real-world IoT ecosystems, where balancing speed and reliability is a critical factor
Keywords: lightweight encryption; cryptanalysis; hybrid attacks; cipher evaluation; SPN architecture